2016
DOI: 10.1371/journal.pone.0169303
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Serotonin Transporter Inhibition by Toll-Like Receptor 2 Activation. A Feedback Modulation

Abstract: TLR2 is a microbiota recognition receptor that has been described to contribute to intestinal homeostasis and to ameliorate inflammatory intestinal injury. In this context, serotonin (5-HT) has shown to be an essential intestinal physiological neuromodulator that is also involved in intestinal inflammatory diseases. Since the interaction between TLR2 activation and the intestinal serotoninergic system remains non-investigated, our main aim was to analyze the effect of TLR2 on intestinal serotonin transporter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 53 publications
(68 reference statements)
6
38
0
1
Order By: Relevance
“…This suggests that long-term NOD2 activation may decrease SERT expression via transcriptional and/or post-transcriptional mechanisms, offering an explanation for the 5-HT uptake reduction. In agreement with our results, other PRRs have also demonstrated inhibition of SERT activity with [21,22] or without [30] alteration of SERT expression. The activation of NOD2, with low concentrations of MPD, induces an inhibitory effect observed only in the short (30 minutes) and medium terms (6 hours), suggesting that a brief stimulation of NOD2 induces a rapid inhibition of SERT activity, increasing 5-HT extracellular availability to promote a fast inflammatory response.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This suggests that long-term NOD2 activation may decrease SERT expression via transcriptional and/or post-transcriptional mechanisms, offering an explanation for the 5-HT uptake reduction. In agreement with our results, other PRRs have also demonstrated inhibition of SERT activity with [21,22] or without [30] alteration of SERT expression. The activation of NOD2, with low concentrations of MPD, induces an inhibitory effect observed only in the short (30 minutes) and medium terms (6 hours), suggesting that a brief stimulation of NOD2 induces a rapid inhibition of SERT activity, increasing 5-HT extracellular availability to promote a fast inflammatory response.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, previous results have concluded that TLR2 (either TLR2/1 or TLR2/6) and TLR4 activation decrease significantly 5-HT uptake in Caco-2/TC7 cells [21,22]. Moreover, the over-expression of both receptors has been implicated in IBD [14].…”
Section: Interdependence Among Tlr2 Tlr4 and Nod2 In Caco-2/tc7 Cellssupporting
confidence: 66%
See 3 more Smart Citations